Medicinal plants used in the Amazon region: a systematic review (Research, Society and Development, 2021)
The Amazon region’s biodiversity is exploited by the local population, commonly for therapeutic purposes. Given this information, the goal of this study was to perform a systematic review on medicinal plants used in this region, listing the name of the species, location found, and its importance for traditional medicine and for local people. For this, a search was performed in the PubMed/Medline and Lilacs databases, using the descriptors medicinal plants, Amazonia or Amazon region, in Portuguese, English, and Spanish. The main findings demonstrate that different species from different botanical families are used by the local population. The main therapeutic outcomes sought out refer to the search for relief or treatment of gastrointestinal, hepatic alterations, fever, kidney stones, pain, infections, and parasites. Thus, it is concluded that the practice of traditional medicine is very common in the Amazon region and is transmitted orally from generation to generation. In this practice, the use of medicinal plants in the form of tea is highlighted, with the species in the form of powder, dried or natural plants. Therefore, it is recommended that the strengthening of pharmacological studies involving local medicinal plants can provide scientific support for popular knowledge.